Analysis of Irrigation Water Requirements In The Secondary Channel of Rentang Irrigation Area - Anugrah, Erhan; El Faris, Mustafa; Nurdiyanto, Nurdiyanto (Green Publisher Indonesia, 2025)
Effective management and planning of irrigation systems critically depend on accurately understanding the overall irrigation water requirements. This study aims to evaluate and project the irrigation water needs in the secondary channel of BSD 1, located in the Rentang Irrigation Area, Majalengka Regency, which serves an irrigation area of 620 hectares and is supplied by the Jatigede Dam and Cimanuk River. Factors such as effective rainfall, water layer changes, seepage, consumptive use, and land preparation are considered in determining water needs. The research employs the kp-01 concept, allowing manual calculations to determine irrigation requirements. Results indicate that irrigation water is necessary starting in early November due to the rice planting pattern. The manual calculations reveal a maximum irrigation water requirement of 1.55 m³ per second during the second period of May and a minimum requirement of 0.06 m³ per second during the second period of December. The findings highlight the importance of understanding seasonal variations and optimizing water resource allocation to ensure efficient irrigation practices. This study concludes that adopting precise calculation methods like kp-01 is essential for sustainable irrigation management and can serve as a reference for similar agricultural planning efforts in other regions.